Estudo anatomohistológico do tendão do músculo fibular longo no túnel do osso cuboide: correlação com as dimensões do túnel e a presença do os Peroneum - Ribeiro, Henrique César Temóteo (2019)
The peroneus tendons lesion is a frequent cause of lateral pain and instability of the ankle. Although less frequent, the peroneus longus tendon lesion have been gaining importance in the diagnostic investigation. Mechanical etiopathogenesis is the most common and cuboid bone groove is a friction site. The references of the literature on its anatomopathological considerations are limited. The objective of this study is to define and identify the variations of the morphological aspects of this microregion and its corrrelation with histological alterations of the peroneus longus tendon. A total of 60 tendons and 60 ciboid bones, divided into 3 age groups of 10 corpses (20 tendons / cuboids) were analyzed: Group 1 (15-40 years), Group 2 (41-65 years), Group 3 years). The presence or absence of os peroneum was observed and the dimensions of depth, width and length of the cuboid groove were measured. The tendon was cut at 3 levels: proximal (A), intra (B) and distal (C) to the groove and analyzed histologically, in the staining of Hematoxylin-Eosin (for cell density), and Picrosirius Red (collagen quantification). Age group 1 showed the following number of cells per field on average: in section A 445.08, in section B 590.14 and in section C 575.87. Group 2 in cut A 576.08, cut B 655.67 and cut C 595.67. In Group 3 in the cut A 656.87, in the cut B 685.93 and in the cut C 678.1. In the collagen quantification the percentages of collagen type I and III were measured and statistical analyzes were carried out for correlation of the data in relation to the thickness of the tunnel, age and presence or not of the os peroneum, obtaining correlation of the increase of the percentage of collagen type III with the width and the height of the tunnel and age. The conclusions were that the dimensions of the cuboid groove had no variation between the groups. There was a correlative variation between changes in tunnel (height and width) and age with the increase of cellular density and percentage of collagen type III of the tendon, which may be a cause of mechanical stress and consequent tendinosis or rupture of the peroneus longus tendon.